Composition and abundance of zooplankton community of an impacted estuarine lagoon in Northeast Brazil - Almeida,LR (2012)
Guaraíras Lagoon is a shallow coastal lagoon subject to intense human impacts, including shrimp aquaculture, urban expansion and agricultural activities, and is therefore vulnerable to eutrophication. With the aim of detecting the effects of human-mediated disturbance and environmental change in the lagoon, a spatial-temporal study was conducted in order to assess the actual ecological status of the lagoon and the species composition and density of the mesozooplankton, highlighting copepod assemblages. Algal biomass (chlorophyll-a) and total phosphorus concentration indicated that the lagoon is a meso-eutrophic coastal system in the inner part, and is oligotrophic in the areas influenced by the marine waters. High salinities were recorded in the lagoon, characterizing the lagoon as a coastal-marine ecosystem, rather than true estuarine. Mesozooplankton abundance fluctuated widely and showed marked spatial heterogeneity. The copepod assemblage was characterized by a coastal/estuarine group dominated by Oithona spp., Acartia lilljeborgi and Parvocalanus crassirostris in the inner areas of the lagoon, and a marine group characterized by the copepods Paracalanus quasimodo, Calanopia americana, Corycaeus (C.) speciosus and Monstrilloida in the area of marine influence. Thus, the spatial variability in the distribution of mesozooplankton species can be ascribed to the presence of a horizontal gradient of salinity and trophic conditions. Overall, the results showed that spatial variation in the water physicochemical characteristics of Guarairas Lagoon have significant effects on the structure and repartition of the mesozooplankton assemblages, which may potentially affect the functioning and biodiversity of this coastal ecosystem.